From threat to safety: Instructed reversal of defensive reactions. (24th September 2014) - Costa, Vincent D.; Bradley, Margaret M.; Lang, Peter J.
Abstract Cues that signal the possibility of receiving an electric shock reliably induce defensive activation. To determine whether cues can also easily reverse defensive reactions, a threat reversal paradigm was developed in which a cue signaling threat of shock reversed its meaning across the course of the study. This allowed us to contrast defensive reactions to threat cues that became safe cues, with responses to cues that continued to signal threat or safety. Results showed that, when participants were instructed that a previously threatening cue now signaled safety, there was an immediate and complete attenuation of defensive reactions compared to threat cues that maintained their meaning. These findings highlight the role that language can play both in instantiating and attenuating defensive reactions, with implications for understanding emotion regulation, social communication, and clinical phenomena.